Understanding the Heartwork of Indigenous Student Services during the Challenging Times of Reconciliation, Decolonization, and Indigenization - Waterman, Stephanie J.; Cunningham, Shawna M.; Pidgeon, Michelle (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur, 2025)
Indigenous Student Centres (ISCs) are student affairs units specialized to serve Indigenous students and communities. These Centres are places of significance on campus for Indigenous students for their cultural relevance and embodiment of Indigenous ways of being. Professionals working in and with ISCs ground their work firmly in Indigenous Knowledges that often evoke distinct cultural protocols and ways of being. Kirkness and Barnhardt’s (1991) 4Rs of Respect, Relevance, Reciprocity, and Responsibility and Archibald’s (2008) Indigenous storywork are the foundation of the co-authors’ research with ISC staff and administrators. The history of Indigenous academic programming is shared to provide the foundation for the evolution of ISCs. The co-authors explore how ISCs holistically support Indigenous students while encountering resistance and systemic challenges, such as cultural illiteracy, by non-Indigenous units and reconciliation fatigue. They conclude with suggestions for supporting reconciliation work as an ally or good neighbour.